H2S adsorption from biogas using natural Clinoptilolite - Pourzolfaghar, Hamed (2012)
Adsorption of H2S by solids fixed in a bed column is the most efficient,environmental friendly, and economical process compared to other technologies. It can be studied through three different approaches; (1) Modeling (2) Laboratory scale experiments and (3) Pilot scale experiments. Many laboratorial scale experiments proved that the Clinoptilolite is a promising medium to be used as an adsorbent of H2S from gas streams at low temperatures whereby few of them are focused to inspect usage of this material in its natural form. Using natural Clinoptilolite may results into a dramatic decrease of the adsorption process costs if its efficiency and performance during the process could be satisfied. In this study, H2S removal efficiency of Clinoptilolite is surveyed at ambient temperature and atmospheric pressure during experiments on a biogas produced directly from an anaerobic digester. An adsorption column unit designed and fabricated for this study by ASEPTIC Sdn Bhd contains three fixed bed columns, flow rate and pressure control,and gas sampling systems. The experiments can be categorized into two main subjects; (1) Key experiments (2) Supplementary experiments. The key experiments results show that according to the developed optimized conditions of the process,adsorption efficiency is 43.44%. This adsorption efficiency rate could be increased up to 94% at supplementary experiments by applying the time duration between the experiments. Other process characteristics like intrinsic regeneration and CH4/CO2 upgrading ratio were interpreted using analytical equipment results like FTIR, EDX,SEM, BET and XRD. Besides, in order to catch a relationship between different parameters and measured experimental data, a data fitting was performed using Microsoft Excel software.